Stock returns and implied volatility: A new VAR approach - Bong Soo Lee; Doojin Ryu (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
The authors re-examine the return-volatility relationship and its dynamics under a new vector autoregression (VAR) identification framework. By analyzing two model-free impliedvolatility indices - the well-established VIX (in the United States) and the recently published VKOSPI (in Korea) - and their stock market indices, the authors find an asymmetric volatility phenomenon in both the developed and emerging markets. However, the VKOSPI shows impulse response dynamics that are quite different from those of the VIX. This finding can be attributed to the unique characteristics of the KOSPI200 options market, which determine the dynamics of the VKOSPI.
Keywords: G10; G15; 330; asymmetric volatility; vector autoregression; VIX; VKOSPI; Kapitalertrag; Börsenkurs; Volatilität; Aktienindex; VAR-Modell; USA; Südkorea